PRE-SCHOOL CURRICULUM: IMPLEMENTATION CHALLENGES (Practitioner Research, 2021)
Early Education is vital for the continuous learning of children. Preschool teachers play their role and are also responsible for implementing teaching and learning, using the National Preschool Curriculum and Assessment Standard Document (DSKP KSPK). However, there are constraints in the implementation of the DSKP KSPK. This article aims to present the challenges faced by pre-school teachers in teaching and learning in pre-schools. The challenges faced include external and internal factors. External aspects involve the nation’s policy and leadership, trust and societal culture and school administrators. Internal challenges include teachers’ readiness regarding knowledge in the area, level of understanding, skills and attitude. In conclusion, previous studies also present challenges that require continuous training to be given to teachers and administrators to strengthen early childhood education.